1978
DOI: 10.1079/bjn19780156
|View full text |Cite
|
Sign up to set email alerts
|

The effects of folic acid supplementation during pregnancy in the rat

Abstract: I . Twenty-four Sprague-Dawley female rats were randomly assigned to three groups (groups A, B, C). Group A was given a folic acid-free diet and groups B and C received 0.0018 g folic acid/kg diet. Rats in g-oup C were also given a supplement of I mg folic acid/d by intraperitoneal injection.2 . After 14 d of feeding the rats were mated. The diets were continued throughout gestation. On day 2 1 , of gestation the dams were killed and their livers and products of conception assayed for RNA, DNA, protein and tet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1981
1981
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…a Maternal betaine supplementation increased IGF2 expression in the hippocampus of newborn piglets, then enhanced the downstream signaling molecule p-ERK1/2 and the up-regulation of the proliferation and anti-apoptotic markers, b maternal betaine supplementation increased the betaine/ methionine metabolism induced the hypermethylation of DMRs of the IGF2 gene locus in the hippocampus the hippocampal DNA content was significantly increased in the prenatally betaine-supplemented piglets. This is in line with a previous report that maternal supplementation of folic acid (a methyl donor) from 14 days before mating till the end of pregnancy increased DNA content in the placenta and liver of rat fetuses [41] and also agrees with the notion that higher maternal choline intake is associated with improved neurogenesis in the fetal hippocampus and enhanced memory performance in adult life [42]. In accordance with the increased DNA content, the hippocampal expression of proliferation and anti-apoptotic markers (Ki67, PCNA, CCD2 and Bcl-2) was significantly up-regulated in the neonatal piglets born to betaine-supplemented sows.…”
Section: Discussionsupporting
confidence: 93%
“…a Maternal betaine supplementation increased IGF2 expression in the hippocampus of newborn piglets, then enhanced the downstream signaling molecule p-ERK1/2 and the up-regulation of the proliferation and anti-apoptotic markers, b maternal betaine supplementation increased the betaine/ methionine metabolism induced the hypermethylation of DMRs of the IGF2 gene locus in the hippocampus the hippocampal DNA content was significantly increased in the prenatally betaine-supplemented piglets. This is in line with a previous report that maternal supplementation of folic acid (a methyl donor) from 14 days before mating till the end of pregnancy increased DNA content in the placenta and liver of rat fetuses [41] and also agrees with the notion that higher maternal choline intake is associated with improved neurogenesis in the fetal hippocampus and enhanced memory performance in adult life [42]. In accordance with the increased DNA content, the hippocampal expression of proliferation and anti-apoptotic markers (Ki67, PCNA, CCD2 and Bcl-2) was significantly up-regulated in the neonatal piglets born to betaine-supplemented sows.…”
Section: Discussionsupporting
confidence: 93%
“…When maternal calorie intake is restricted only in late gestation, the weight of the rat placenta is unaffected, although the fetus may still be growth restricted (Ahokas et al 1981(Ahokas et al , 1983Lesage et al 2001). A few studies have investigated the placental effects of dietary micronutrient content and shown that substances such as branched chain amino acids, iron and folic acid can influence placental and fetal weight, especially when added as supplements to low-protein diets (Morgan and Winick 1978;Lewis et al 2001a;Mogami et al 2009). In addition, recent studies have demonstrated that feeding mice a diet rich in fat and sugar throughout pregnancy reduces growth of the placenta and fetus near term ).…”
Section: Environmental Regulation Of Placental Sizementioning
confidence: 99%
“…The requirements for folates likely are highest in organs in which cell turnover or cell division is rapid. Supplemental folic acid was shown to increase RNA, DNA and protein content of rat fetuses (Morgan and Winick, 1978) and to prevent embryonic death in guinea-pigs (Habibzadeh et al, 1986). Furthermore, RNA concentration is correlated with survival in 1-to 12-d-old pig embryos (Martinenko, 1977); it appears, therefore, that maternal folic acid nutrition must be 724 adequate to prevent embryonic mortality in polytocous species.…”
Section: Introductionmentioning
confidence: 99%